2019
DOI: 10.1086/704945
|View full text |Cite
|
Sign up to set email alerts
|

Reinvestigation of the Enigmatic Carboniferous Sphenophyte StrobilusCheirostrobusScott and Implications of In SituRetusotriletesSpores

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Other spore taxa with implications for vegetation reconstruction are Retusotriletes rotundus , documented from the plant genera Crenaticualis and Sawdonia (Gensel 1980; Hotton et al 2001), and Retusotriletes cf. triangulatus , documented from Asteroxylon , Psilophyton and Tricherophyton (Gensel 1980; Wellman 2018; Neregato and Hilton 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Other spore taxa with implications for vegetation reconstruction are Retusotriletes rotundus , documented from the plant genera Crenaticualis and Sawdonia (Gensel 1980; Hotton et al 2001), and Retusotriletes cf. triangulatus , documented from Asteroxylon , Psilophyton and Tricherophyton (Gensel 1980; Wellman 2018; Neregato and Hilton 2019).…”
Section: Resultsmentioning
confidence: 99%
“…These rocks outcrop in cliff sections at Pettycur and at Kingswood End to the west, as well as in the intervening Pettycur Caravan site (Rex and Scott 1987). The nearby Pettycur limestone flora has been described in numerous publications (Scott et al 1984;Rex and Scott 1987;Neregato and Hilton 2019). Palynological dating of the Kinghorn Volcanic Formation has indicated that it belongs to the Raistrickia nigra-Triquitrites marginatus (NM) and Tripartites vetustus-Rotaspora fracta (VF) miospore zones (Brindley and Spinner 1989) of mid to late Asbian to early Brigantian regional substages of the Viséan stage (Monaghan and Pringle 2004), with absolute ages between 329 and 335 Ma (Monaghan and Pringle 2004;Monaghan and Browne 2010).…”
Section: Geological Settingmentioning
confidence: 98%